Edukasi dan Latihan Relaksasi Otot Progresif untuk Menurunkan Tekanan Darah dan Mengurangi Tingkat Stres Klien Hipertensi di Desa Tambak Cemandi - Made Indra Ayu Astarini; Ira Ayu Maryuti; Kristina Pae; Steven Aldo Marcelo (LPMP Imperium, 2026)
Hypertension affects approximately 30% of the population in Sedati District, with Tambak Cemandi Village representing a community characterized by a high proportion of elderly residents. Interviews with the local midwife indicate that around 100 elderly individuals regularly participate in elderly health post (posyandu lansia) activities, the majority of whom are affected by hypertension. In response to this, a community service initiative was implemented to deliver targeted education on complementary therapy, specifically progressive muscle relaxation, as a strategy to support blood pressure and stress reduction among elderly individuals with hypertension. The intervention employed a structured approach, incorporating lectures, demonstrations, and interactive discussions. Facilitators provided direct instruction and demonstration of the progressive muscle relaxation technique, followed by participant practice to reinforce skill acquisition. Of the 68 participants, 77% exhibited hypertension with blood pressure exceeding 130/80 mmHg, and 76% reported moderate stress levels. Post-intervention, participants demonstrated the ability to independently perform progressive muscle relaxation and reported subjective improvements in comfort, with the potential for continued practice at home using facilitator-provided materials. These findings suggest that education and training in progressive muscle relaxation can enhance knowledge and self-management capabilities among elderly individuals with hypertension, supporting blood pressure control alongside pharmacological treatment.